(untitled) (Evidence-Based Pharmacotherapy in Clinical Practice, 2025)
Author Mr. Kiran Sai Kumar Jonnada PharmD Intern, Department of Pharmacy Practice, Koringa College of Pharmacy, Korangi, Andhra Pradesh, India Abstract Current pharmacological management of cardiovascular disorders encompasses multiple drug classes targeting specific pathophysiological mechanisms. Hypertension treatment follows stepped-care algorithms incorporating angiotensin-system modulators, calcium channel blockers, and diuretics based on patient characteristics and comorbidities. Heart failure management utilizes mortality-reducing agents including beta-blockers, ACE inhibitors, and mineralocorticoid antagonists, with careful monitoring of hemodynamic parameters and organ function. Coronary artery disease interventions focus on anti-ischemic therapy, antithrombotic agents, and risk factor modification. Arrhythmia management requires careful selection of antiarrhythmic drugs based on specific rhythm disorders, structural heart disease, and proarrhythmic risk. Anticoagulation protocols incorporate direct oral anticoagulants and vitamin K antagonists with systematic monitoring of efficacy and bleeding risk. Drug selection considers specific cardiovascular risk factors, target organ damage, and concomitant conditions Keywords: Cardiovascular pharmacotherapy, Antihypertensive therapy, Heart failure treatment, Antiarrhythmic drugs, Anticoagulation management VIEW PDF